MOBILE SEARCHING RUANG INAP KOSONG RUMAH SAKIT DENGAN METODE BLIND SEARCH - Andika Vebrina; Cut Yunina Eriva (Politeknik Aceh, 2015)
The hospitalis closely related to improve the human health quality, especially for the people who live in Aceh, which has health insurance facilities such as ASKES, Jamkesnas and Jaminan Kesehatan Aceh (JKA). In order to realizeand provide the better health services,it is made anapplication whichcan help the peopleto knowthe availability ofthe inpatient room via mobile phone. The results ofthis system can help family of the patients to make the right decisionin choosing the good hospitalbased onthe patient's conditionandthe availability of the inpatient room. This system isan android-based mobile, andis madeby using the techniqueof JSON data parserandthe blind search method.